The use of bimolecular fluorescence complementation (BiFC) to investigate the functional implications of neuropeptide Y receptor dimerisation and beta-arrestin recruitment - Kilpatrick, Laura Elise (2015)
The functional significance of G protein coupled receptor (GPCR) dimerisation remains debatable partly due to the inability to assign pharmacological properties directly to defined dimers. To address this problem, this thesis uses bimolecular fluorescence complementation (BiFC), whereby protein-protein interactions are identified by the fluorescence generated from the association of complementary fluorescent protein fragment tags. The irreversibility of BiFC constrains receptor complexes of precise composition. The 4 Y receptor family members were chosen as model GPCRs as their relative β-arrestin recruitment and regulation by endocytosis remains questionable. BiFC based high content imaging assays quantified the pharmacology of β-arrestin2 recruitment to Y receptors, which correlated with their agonist induced endocytosis (Chapter 3). Targeted mutagenesis, showed key intracellular receptor domains shared in arrestin recruitment and internalisation. Fluorescence recovery after photobleaching, and fluorescence correlation spectroscopy measured the diffusion of fluorescent Y receptor complexes and showed agonist stimulation slowed receptor motility (Chapter 4). A novel BiFC system allowed the correlation of this slowed motility with the behaviour of defined Y receptor/arrestin signalling complexes. BiFC also constrained Y1 receptors or β2-adrenoceptors as dimers of precise composition. Quantitative platereader imaging, measured BiFC dimer internalisation as an indirect readout of β-arrestin recruitment and dimer function (Chapters 5 and 6). Selective mutagenesis showed occupation of a single ligand binding site and the presence of one phosphorylated C terminal domain was sufficient, implying symmetrical binding of β-arrestin to Y1 receptor dimers. Finally Y1/Y5 receptor BiFC heterodimers showed modified pharmacology not evident for other heterodimer combinations. The most striking alterations were switching of Y5 selective antagonists from surmountable to insurmountable antagonism and the ineffectiveness of Y1 antagonists at inhibiting Y1/Y5 dimer responses, suggesting allosteric interactions between the respective protomers. Previous anti-obesity therapies targeting either Y1 or Y5 subtypes have lacked long term efficacy. However novel responses of the Y1/Y5 dimer, and the use of BiFC to screen for selective antagonism, may help identify future treatments for obesity.